Review of the impact of donor characteristics on pediatric heart transplant outcomes. (21st March 2020) - Conway, Jennifer; Ballweg, Jean A.; Fenton, Matthew; Kindel, Steve; Chrisant, Maryanne; Weintraub, Robert G.; Danziger‐Isakov, Lara; Kirk, Richard; Meira, Oliver; Davies, Ryan R.; Dipchand, Anne I.
Abstract: Heart transplantation (HTx) is a treatment option for end‐stage heart failure in children. HTx is limited by the availability and acceptability of donor hearts. Refusal of donor hearts has been reported to be common with reasons for refusal including preexisting donor characteristics. This review will focus on the impact of donor characteristics and comorbidities on outcomes following pediatric HTx. A literature review was performed to identify articles on donor characteristics and comorbidities and pediatric HTx outcomes. There are many donor characteristics to consider when accepting a donor heart. Weight‐based matching is the most common form of matching in pediatric HTx with a donor‐recipient weight ratio between 0.7 and 3 having limited impact on outcomes. From an age perspective, donors <50 years can be carefully considered, but the impact of ischemic time needs to be understood. To increase the donor pool, with minimal impact on outcomes, ABO‐incompatible donors should be considered in patients that are eligible. Other factors to be considered when accepting an organ is donor comorbidities. Little is known about donor comorbidities in pediatric HTx, with most of the data available focusing on infections. Being aware of the potential infections in the donor, understanding the testing available and risks of transmission, and treatment options for the recipient is essential. There are a number of donor characteristics that potentially impact outcomes following pediatric HTx, but these need to be taken into consideration along with their interactions with recipient factors when interpreting the outcomes following HTx.